Deutschlands Wirtschaft, seine Schulden und die Unzulänglichkeiten der einheitlichen Geldpolitik im Eurosystem; Germany's economy, its debts, and the shortcomings of the Eurosystem's common monetary policy - Dieter Spethmann; Otto Steiger (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
– In 2004, Germany became Europe's `king of debt' in absolute figures, thereby leaving behind even Italy, for decades the bearer of this awkward title. However, Germany's rising public debt is not due to loose fiscal policy but the result of the common monetary policy in European Monetary Union (EMU). While Germany has the lowest rate of inflation in EMU, it has to pay the same nominal rate of interest as its competitors, that is, it has to shoulder the by far highest real rate of interest. This in turn has led to economic stagnation, with decreasing tax revenues and, in spite of huge efforts to reduce public expenditures, rising debts. As Germany is still the biggest economy in Europe, its stagnation has decisively contributed to EMU's slow economic growth. According to the authors, the not so pleasant state of Euroland is due to the fact that EMU is not an `optimal currency area' (Robert Mundell). EMU does not fulfil one of the most important criteria for optimality: the absence of tremendous differences between its member countries' real rates of interest. In the paper, several measures of how to overcome the German problem are discussed, especially how to reconstruct the Eurosystem, the decentralised central banking system of EMU, to allow for a differentiated monetary policy, with high (low) nominal rates of interest for high (low) inflation countries. Drawing on a proposal by Erik Lindahl in 1930, this would mean to re-establish the European Central Bank (ECB) as the central monetary authority in the Eurosystem, with the monopoly to issue money. In spite of its name, the ECB is not a bank of issue, not to speak of being a lender of last resort, but only a co-ordinating agent between the Council of Governors of the Eurosystem, the decisive institution for monetary policy in EMU, and the twelve national central banks who alone issue the Euro. An alternative proposal discussed is to assign to the strongest central bank in the Eurosystem, the Bundesbank, the role of the Federal Reserve Bank of New York in the Federal Reserve System, thereby transforming the Eurosystem into a European Reserve System of Federal States. However, the strengthening of the ECB, or the Bundesbank, needs the support of a central fiscal authority in EMU, a role which today's EG Commission in Brussels cannot shoulder : it disposes only of a tiny amount of EMU's aggregate tax revenues. The authors are aware of the political difficulties to re-organise the Eurosystem. However, if politicians shy away from such a reform, the only option for solving Germany's stagnation should be to leave EMU.
Keywords: E58; F42; E58; F42; 330; Öffentliche Schulden; Europäische Wirtschafts- und Währungsunion; Realzins; Inflation; Internationaler Wettbewerb; Geldpolitik; Reform; Deutschland; EU-Staaten